우리나라 당뇨병의 역학적 특성 -대한당뇨병학회,건강보험심사평가원 공동연구 결과를 중심으로 - 박이병; Ie Byung Park; 백세현; Sei Hyun Baik (Diabetes & metabolism journal, 2009)
The aim of article is to introduce the current status of diabetes care and characteristics in diabetic patients in Korea, which is a joint report by Korean Diabetes Association (KDA) and Health Insurance Review Agency (HIRA) ("Diabetes in Korea 2007") and to review the recent published data about the current status of diabetes mellitus in Korea. (Korean Diabetes J 33:357-362, 2009)